Association Between Nonthyroidal Illness Syndrome and Disseminated Intravascular Coagulation in Sepsis - Yao Y; Li J; Sun W; Ma C; Ning N; Li J; Ni T; Gui M; Chen Y; Zhao B; Zhang J; Zhu J; et al. (Journal of Inflammation Research, 2024)
Yi Yao,1,* Juan Li,2,* Wenwu Sun,1,* Chaoping Ma,2,* Ning Ning,1 Jiaoyan Li,1 Tongtian Ni,1 Menglu Gui,1 Ying Chen,1 Bing Zhao,1 Jiyuan Zhang,2 Jiyue Zhu,3 Chengjin Gao,2 Huiqiu Sheng,1 Enqiang Mao1 1Departments of Emergency, Ruijin Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, 200025, People’s Republic of China; 2Department of Emergency, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China; 3Department of General Surgery, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huiqiu Sheng, Departments of Emergency, Ruijin Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, 200025, People’s Republic of China, Tel +86-15801971839, Email shenghq803@163.com Chengjin Gao, Department of Emergency, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China, Tel +86-18221088783, Email gaochengjin@xinhuamed.com.cnPurpose: Both nonthyroidal illness syndrome (NTIS) and disseminated intravascular coagulation (DIC) are commonly occurred in sepsis. The objective of this study is to evaluate the association between NTIS and DIC, as well as their impacts on the mortality in adults with sepsis.Patients and methods: A total of 1219 septic patients in two Chinese academic centers from October 2012 and October 2022 were enrolled in analysis. We conduct logistic regression models to analyze the independent risk factors for DIC. Modified Poisson regression models are used to estimate the relative risk (RR) of NTIS on the 28 days mortality in septic patients with DIC. Correlation analysis between thyroid function parameters and coagulation parameters is performed with Pearson coefficient be reported.Results: DIC is diagnosed on 388 (31.8%) of all the 1219 enrolled septic patients within 72 hours after admission. In multivariate logistic regression models, NTIS (OR 3.19; CI 2.31– 4.46; p< 0.001) is a statistically significant independent risk factor for DIC after adjustment for potential confounders. Twenty-eight days mortality is significantly higher in DIC patients complicated with NTIS compared with the other DIC patients (23.2% vs 14.0%, p=0.024). This result is also robust in different modified Poisson regression models (Model 1: RR 1.46; CI 1.25– 1.70; p< 0.001; Model 2: RR 1.35; CI 1.14– 1.60; p< 0.001; Model 3: RR 1.18; CI 1.02– 1.37; p=0.026). Correlation analysis reveals that the thyroid function parameters of FT3, FT4 and TSH only have weak correlations with coagulation parameters of platelet count, fibrinogen, FDP, D-dimers, PT, APTT and INR in sepsis.Conclusion: NTIS is an independent risk factor for DIC in adults with sepsis. DIC patients complicated with NTIS have significantly higher severity and higher rate of mortality.Keywords: sepsis, low T3 syndrome, nonthyroidal illness syndrome, thyroid function, disseminated intravascular coagulation